Teachers' experiences in overcrowded classrooms in Egyptian public schools - Ayoub, Ghada Mamdouh (AUC Knowledge Fountain, 2019)
Overcrowded classrooms are one of the main problems in the Egyptian educational system. It was reported in 2018 that the average number of students per class in the primary stage is 46 students, the preparatory stage 43 students and the general secondary stage 39 students. Hence, the study focuses on teachers’ experience regarding over-crowded classrooms and how its consequences affect the quality of public education in Egypt; it looks into the reasons behind this problem from the teachers’ perspectives. The participants are thirty-seven primary school teachers from four different schools. One of these schools is an experimental language school and the remaining are three governmental public schools. The study adopts a qualitative design by using an open-ended questionnaire. Thematic analysis was selected to analyse the findings; themes such as: Teaching experience is stressful in overcrowded classes, Students’ participation rate, unavailable resources, teaching strategies and disruptive behaviour were deduced from the findings of the study. Finally, this study presents some practical implications and recommendations for future research.